Efficacy of intra-articular injection of Steroid plus High Molecular Weight Hyaluronate in Primary Osteoarthritis of the Knee in a Tertiary Care Hospital in Eastern India (Student's Journal of Health Research Africa, 2025)
BackgroundKnee primary osteoarthritis is a degenerative joint disease creating pain and stiffness, and disability among elderly people. Non-surgical therapies can be effective in offering partial disease-modifying and unpredictable symptomatic relief.  The objective of the study was to assess the effectiveness of intra-articular steroid with high molecular weight hyaluronate in the reduction of pain and patient-reported outcomes.MethodsThe proposed interventional study was an 18-month prospective study in the Department of Physical Medicine and Rehabilitation at IPGME & R, SSKM Hospital, Kolkata, India. The inclusion and exclusion criteria were used to recruit fifty patients with primary knee osteoarthritis. A single intra-articular injection of steroid and high molecular weight hyaluronate was administered to all the patients. Pain was measured by the use of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain scale, and overall well-being was measured by the Patient Global Assessment scale. At the baseline, six weeks, and twelve weeks, the evaluations were conducted. The Tukey multiple comparison test was conducted as a statistical test.ResultsBoth the WOMAC pain scores and Patient Global Assessment scores were significantly different at six weeks and twelve weeks versus the baseline. The data on the mean differences showed a clinically significant decrease in pain and better patient-reported outcomes. Nonetheless, no significant increase in the interval between six and twelve weeks was observed, indicating that most improvement in symptoms took place during the first six weeks, and beyond was not significant.ConclusionsIntraarticular injection of steroid plus HMWH in primary OA knee is effective in terms of reduction of pain in the WOMAC scale and reduction of Patients Global Assessment scale, and negligible adverse effect occurs in this regimen.RecommendationFuture multi-center randomized controlled trials with a larger sample and longer follow-up should verify these results.
Keywords: Intraarticular injection; Intraarticular High Molecular Weight Hyaluronate; Intraarticular steroid; Primary Osteoarthritis knee